Corporal punishment and externalizing behaviors in toddlers: positive and harsh parenting as moderators - Mendez, Marcos D. (Kansas State University, 2013)
Controversy still exists in whether parents should or should not use corporal punishment to discipline their young children. The aim of this study was to investigate whether corporal punishment when the child was two years old predicted child externalizing behaviors a year later, and whether or not this association was moderated by parents’ observed positivity and harshness towards their child. A total of 218 couples and their first born child were selected for this study from the Family Transition Project (FTP) data set. Findings indicated that frequency of fathers’ corporal punishment when the child was two years old predicted child externalizing behaviors a year later, while controlling for initial levels of child externalizing behavior. Also, it was found that observed positive parenting and observed harsh parenting moderated the relationship between corporal punishment and child externalizing behaviors. These results highlight the importance of continuing to examine the efficacy of a commonly used form of discipline (i.e., corporal punishment). Furthermore, this study suggests that the parental climate in which corporal punishment is used may also be important to consider because parental positivity and harshness attenuate and amplify, respectively, the association of corporal punishment with child externalizing. Implications for family therapy are offered.
Keywords: Corporal Punishment; Spanking; Slapping; Externalizing Behaviors; CBCL; Family Transition Project; Ecology (0329)